El coste de los cuidados de larga duración en la población espa\~nola: Análisis comparativo entre los a\~nos 1999 y 2008 - Manuela Alca\~niz Zanón; Ramón Alemany Leira; Catalina Bolancé Losilla; Monserrat Guillén Estany (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– This paper analyzes the cost of long-term care (LTC) associated to individuals in dependence situation. The economic cost of care per unit of service is linked to the expected time of needed care and the intensity of required services. We have estimated the expected lifetime cost of LTC in dependence for individuals aged 65 years and above. Calculations have been made separately for men and women. The estimations have been done for year 1999 and 2008, respectively, using data from the two offcial surveys carried out by the Spanish Institute of Statistics (INE). Offcial mortality records and life table trends were used to create realistic scenarios for longevity. We have made comparisons between 1999 and 2008 results, and we have also analysed the last decade trends for longevity, for prevalence of dependence, and for the expected costs of long-term care. We have studied the effects on the evolution of the costs of long-term care due to increasing in longevity and prevalence of dependence and, finally, and separately, we analyzed the effect of the inflation.
Keywords: I13; I18; C14; C15; 330; dependency; costs of long-term-care; life expectancy; prevalence rate of dependence